An in‐frame pseudoexon activation caused by a novel deep‐intronic variant in the dysferlin gene. Issue 2 (21st December 2022) - Sun, Chengyue; Xie, Zhiying; Cong, Lu; Xu, Yan; Liu, Zunjing
Abstract: The precise detection and interpretation of pathogenic DYSF variants are sometimes challenging, largely due to rare deep‐intronic splice‐altering variants. Here, we report on the genetic diagnosis of a male patient with dysferlinopathy. He remained genetically unsolved after routine exonic detection approaches that only detected a novel heterozygous frameshift variant (c.407dup, p.Thr137Tyrfs*11) in DYSF exon 5. Via muscle‐derived DYSF mRNA studies, we identified a novel deep‐intronic DYSF variant in the other allele (c.1397 + 649C > T), which causing in‐frame alterations in DYSF mRNA and protein structure and confirmed his genetic diagnosis of dysferlinopathy. Our study emphasizes the potential role of undetected deep‐intronic splice‐altering variants in monogenic diseases.